(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the outcome of lateral supramalleolar flap for soft tissue coverage in patients with exposed heel and dorsum of foot. Methodology: This prospective study was conducted in Department of Orthopaedic Surgery, Bahawal Victoria Hospital Bahawalpur from 1st April 2008 to 30th June 2009. Lateral Supramalleolar Flap was used in total of 20 cases for soft tissue coverage of heel and dorsum of foot. All patients discharged on 5th day after flap surgery. First follow up in outpatient department was scheduled ten days after discharge and skin sutures were removed, then patients were followed on every 5th day for two months. Results: Eighteen cases of soft tissue defects of heel region and two cases of dorsum of foot were covered with supramalleolar flap. There were sixteen cases of soft tissue defects of heel after trauma, two cases of chronic heel ulcer and one of chronic osteomyelitis. All cases of soft tissue defects of dorsum of foot were because of trauma. Flap survived in all cases. Only in four cases marginal necrosis was seen which were used to cover heel. Flap was debrided and advanced in three cases while other needed split thickness skin grafts. Mild flap edema occurred only in six cases, which resolved only by elevation of limb. Conclusion: Lateral supramalleolar flap is a very effective tool for reconstructing the soft tissue defects in dorsum of foot and heel region.